2019
DOI: 10.1055/s-0039-1694904
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl Sulfoxide Leads to Decreased Osteogenic Differentiation of Stem Cells Derived from Gingiva via Runx2 and Collagen I Expression

Abstract: Objectives Dimethyl sulfoxide (DMSO) plays various functions, including cellular functions such as cellular growth. The aim of this study was to evaluate the effects of DMSO on the proliferation and osteogenic differentiation of human gingiva-derived stem cells. Materials and Methods Stem cells derived from gingiva were cultured in the presence of DMSO at concentrations ranging from 0.01 to 10%. Statistical Analysis We performed a one-way analysis of variance (ANOVA) with post hoc test to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…An anthraquinone dye assay were used for calcium deposit evaluation to assess osteogenic differentiation on Days 4, 7 and 14 [ 22 ]. Spheroids were washed thrice with phosphate-buffered saline and then cell spheroids were fixed in 4% paraformaldehyde in phosphate-buffered saline at room temperature for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…An anthraquinone dye assay were used for calcium deposit evaluation to assess osteogenic differentiation on Days 4, 7 and 14 [ 22 ]. Spheroids were washed thrice with phosphate-buffered saline and then cell spheroids were fixed in 4% paraformaldehyde in phosphate-buffered saline at room temperature for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…(2015) investigated the effects of different concentrations of DMSO from 0.05 to 1.0 mmol L −1 on odontoblast‐like MDPC‐23 cells and reported that cell viability was not affected by DMSO at any concentration. In a study by Lee & Park (2019), 3% and 10% DMSO caused a decrease in cell viability. In the present study, 1% DMSO was used to dissolve RSV.…”
Section: Discussionmentioning
confidence: 95%
“…For example, it has already been shown that DMSO can affect cell cycle [ 6 10 ], mitochondrial function [ 5 , 11 ], and the epigenetic landscape of various cell types [ 12 14 ]. More importantly, DMSO can prime the differentiation of various types of stem cells [ 7 , 15 18 ], and it is able to sustain mESC culture pluripotency in the absence of LIF [ 20 ]. However, in most of these studies, the range of DMSO concentrations used is not broad and is usually close to 1%, which is a much higher concentration than the amount of DMSO used in the majority of the in vitro biological studies published.…”
Section: Discussionmentioning
confidence: 99%
“…However, DMSO is also a hydrogen-bound disrupter, an intercellular electrical uncoupler, and a hydroxyl radical scavenger, among other properties [ 1 , 3 ], and could conceivably affect cell culture, depending on the cell type and the concentration used, issues that are usually overlooked. For instance, it has already been shown that apart from inducing cytotoxicity [ 4 6 ], DMSO can affect cell cycle [ 6 10 ] and mitochondrial function [ 5 , 11 ], as well as the epigenetic landscape of different cell types [ 12 14 ], and influence the differentiation of various types of stem cells [ 7 , 15 18 ]. Indeed, in 2012, Pal and colleagues reported that when exposing differentiating human embryonic stem cells (hESCs) to three different concentrations of DMSO, there was a dose-dependent downregulation of pluripotency markers and that the lowest concentration biased the differentiation process by enhancing mesodermal differentiation [ 17 ].…”
Section: Introductionmentioning
confidence: 99%